Gender identities and female students’ learning experiences in studying English as Second Language at a Pakistani University - Irfan Ahmed Rind (Cogent Education, 2015)
This paper attempts to examine how female students’ roles as learners are influenced by their socially constructed gender identities and gender roles in studying English as Second Language (ESL) at a public sector university of Pakistan. The aim is to understand how female students’ gender identities and gender roles affect their learning. With an interpretivist epistemological stance, qualitative approach has been used to collect and analysis data. Twenty-five female students of diverse education and family backgrounds were interviewed and observed several times. The findings suggest female students’ gender identities can act to limit their actions and interactions with textbooks, peers and teachers. However, some female students seemed to challenge their socially structured identities. Against certain social norms, they were found to exercise their choice and agency, though such autonomy is limited and conditioned.